Pengembangan Produk Krim Biskuit Rasa Lemon dengan Pewarna Lemak Bubuk dan Olein Minyak Sawit Merah - Maria Afrida; Nuri Andarwulan; Dede Robiatul Adawiyah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Biscuit cream is an emulsion product which contains fat, sugar, and other ingredients, like milk powder, flavouring, and colorant. Indonesia, as the largest palm oil producer in the world, has a great potential to developed palm oil-based biscuit cream product. One potential product for developed is biscuit cream lemon with red palm oil-based fat powder and red palm oil as colorant. This research devided into some steps, i.e fat powder production, characterization of raw materials, determination of biscuit cream-control formula, manufacture of biscuit cream with fat powder and red palm oil as colorant, and physic, chemist, and sensory analysis of biscuit cream. The result showed that fat powder can not be used as the only colorant in biscuit cream because it provides strong unpleasant palm oil aroma, covers lemon flavor and lemon aroma, and harden the biscuit cream texture. Red palm olein then used together with fat powder to provides color and characterization as expected. The result showed that biscuit cream using fat powder and olein MSM has different characterization with biscuit cream control. The result from sensory evaluation of aroma, flavor, and texture profil showed that biscuit cream using fat powder and olein MSM has similiarity with biscuit cream control profil.